Gonococcal epididymo-orchitis in an octogenarian. Issue 4 (3rd July 2020) - Ahmad, Ali; Kusz, Halina
ABSTRACT: Epididymo-orchitis (EO) is inflammation of the epididymis and testicles. In patients older than thirty-five years, it is commonly due to coliform or uropathogenic organisms, whereas younger adults are prone to sexually transmitted infections. We present a relatively infrequent case of gonococcal EO in an octogenarian. This case describes a geriatric male who presented to the emergency department in septic shock. His history was notable for prostate cancer, urinary incontinence and multiple sexual partners. He endorsed perineal pain, localized tenderness with chills and dysuria, and was eventually diagnosed with bilateral EO and hydroceles on repeat ultrasound. PCR was positive for N. gonorrhea. His symptoms responded well to fluid resuscitation and antimicrobial therapy. This case demonstrates that EO secondary to sexually transmitted infections is an important consideration in even the oldest old. It is therefore imperative to obtain a detailed sexual history and identify high-risk sexual behaviors in this population.